Legal analysis of the Fiduciary Agreement between lessor and lessee - Irwan Iwan (Fox Justi : Jurnal Ilmu Hukum, 2026)
As social beings, humans need others in their lives because they cannot live alone. Efforts to fulfill human needs are realized in society through bartering, or exchanging services and goods. The exchange of services and goods is carried out by implementing the terms agreed upon by each party in the cooperative relationship within a contract. Various forms of agreements exist in society, including lease agreements (leasing) and agreements with fiduciary guarantees. Leasing financing requires certain guarantees so that the funds expended by the lessor, plus certain profits, can be repaid by the lessor. In leasing, the capital goods that are the object of the financing agreement serve as collateral for the debt under the financing guarantee. In practice, various possibilities can arise, rendering the lessor's position less secure than initially anticipated. The purpose of this study is to examine the legal analysis of fiduciary agreements between lessors and lessees. The research method used is normative research using primary and secondary legal materials. Legal materials are obtained through library studies such as books, journals, laws and regulations, and other documents related to the research. The results of the study explain that in the Fiduciary agreement between the Lessor and the Lessee, in essence, it is only a loan-borrowing relationship, however, the relationship provides benefits to both parties so that a standard, legal agreement is made so that the agreement is more binding and can be implemented with a full sense of responsibility. Fiduciary registration is mandatory for the fiduciary giver and fiduciary recipient, at the time after the fiduciary agreement is made because if this is not done it will be detrimental to both parties. Therefore, in addition to the deed of agreement with fiduciary guarantees, it is necessary to make another special agreement between the lessor and lessee where the substance of the agreement is to strengthen commitment, responsibility and brotherhood in carrying out the contents of the main agreement.